2016
DOI: 10.1515/rjim-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Changes in Overweight and Obese Patients

Abstract: Background. Obesity and overweight are two pathologies that are more and more frequent in the XXI st century diagnosis and are causing high morbidity and mortality rates in the general population, especially through cardiovascular complications.Aims. Identification and early diagnosis of cardiac changes in overweight and obese patients. Material and method. We carried out a sectional, analytical and observational study on 111 subjects: 27 normal weight subjects and 84 overweight and obese patients, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The importance of screening programs is evident, moreover because some studiesshowed that only overweight itself produce early changes in cardiovascular status of the patient by decreasing the left ventricular ejection fraction, thickening the interventricular septum, increasing left ventricular mass and implementing early diastolic dysfunction [42].Thus, one could expect that cardiovascular disease would be particularly prevalent in patients with overlap syndrome, but there are limited data on this relationship.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of screening programs is evident, moreover because some studiesshowed that only overweight itself produce early changes in cardiovascular status of the patient by decreasing the left ventricular ejection fraction, thickening the interventricular septum, increasing left ventricular mass and implementing early diastolic dysfunction [42].Thus, one could expect that cardiovascular disease would be particularly prevalent in patients with overlap syndrome, but there are limited data on this relationship.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting, positive correlation was found between 6MWT performance and BMI higher than 30 kg/m 2 [18]. This correlation, even paradoxical, is explained by our previous results showing that obese patients often have a better outcome, even though they are more prone cu to cardiac dysfunction and cardiovascular diseases [19], [20]. Maximal exercise capacity or physical capacity may be evaluated by using cardiopulmonary exercise testing (CPET) with a cycle ergometer following standardised protocols, as described recently by Sibilitz et al [21].…”
Section: Assessment Methosds Of the Cardiac Rehabilitation Protocols mentioning
confidence: 85%
“…Because of the COPD comorbidities, like cardiovascular diseases and Obstructive Sleep Apnea (OSA), the importance of screening programs for these pathologies is evident in COPD patients. Some studies showed that only overweight itself produces early changes in cardiovascular status of the patient by decreasing the left ventricular ejection fraction, thickening the interventricular septum, increasing left ventricular mass and implementing early diastolic dysfunction (30). Respiratory muscle training is a part of rehabilitation for stable COPD subjects, as it promotes benefits such as improved pulmonary function and respiratory muscle strength, reduction of dyspnea severity, improved exercise tolerance and enhanced functionality and quality of life.…”
Section: Muscular Training Programmentioning
confidence: 99%